Association of duration of television viewing in early childhood with the subsequent development of asthma. Issue 4 (13th March 2009) - Sherriff, A; Maitra, A; Ness, A R; Mattocks, C; Riddoch, C; Reilly, J J; Paton, J Y; Henderson, A J
Abstract : Objective: To investigate whether duration of television (TV) viewing in young children is associated with subsequent development of asthma. Methods: Children taking part in the Avon Longitudinal Study of Parents and Children (ALSPAC) with no wheeze up to the age of 3.5 years and follow-up data at 11.5 years of age took part in a prospective longitudinal cohort study. The main outcome measure was asthma, defined as doctor-diagnosed asthma by 7.5 years of age with symptoms and/or treatment in the previous 12 months at 11.5 years of age. Parental report of hours of TV viewing per day by the children was ascertained at 39 months. Results: In children with no symptoms of wheeze at 3.5 years of age and follow-up data at 11.5 years of age, the prevalence of asthma was 6% (185/3065). Increased TV viewing at 3.5 years was associated with increased prevalence of asthma at 11.5 years of age (p for linear trend = 0.0003). Children who watched television for >2 h/day were almost twice as likely to develop asthma by 11.5 years of age as those watching TV for 1–2 h/day (adjusted odds ratio 1.8 (95% CI 1.2 to 2.6)). Conclusion: Longer duration of TV viewing in children with no symptoms of wheeze at 3.5 years of age was associated with the development of asthma in later childhood.